The Effect of Price, Relationship Marketing and Word Of Mouth Towards Purchasing Decision - Abbas Moh Afghoni; Mudji Astuti (Universitas Muhammadiyah Sidoarjo, 2021)
This research intended to understand the effect of price, relationship marketing and word of mouth towards purchasing decision on CV. Wonokoyo Gasindo in Beji Pasuruan. This research includes quantitative research with hypothesis test. Sampling in this study was carried out by probability sampling method with the type of simple random sampling with a total of 100 respondents of CV. Wonokoyo Gasindo consumers. Analysis tool used multiple linear regression analysis, classic assumption test, t-test, F test, multiple correlation coefficient and multiple coefficient of determination (R2) by using the SPSS 25.0. version application program. Primary data obtained trough questionnaire whose meassurement uses likert scale. Finally, the data declared valid and reliable. The research results establish that price has an effect to purchasing decision. Relationship marketing has an effect to purchasing decision. Word of mouth has an effect to purchasing decision. Price, relationship marketing and word of mouth have a simultaneously effect to purchasing decision on CV. Wonokoyo Gasindo in Beji Pasuruan.